Cadre Formation of Prospective Islamic Boarding School Leaders through the Khidmah as Ustadz Program at the Mambaul Ulum Bata-Bata Panaan Palengaan Pamekasan Islamic Boarding School - Wakid, Ahmad; Kosim, Muhammad; Atiqullah, H. (Formosa Journal of Applied Sciences, 2024)
Research in this context is motivated by the phenomenon that exists in every Islamic boarding school where there are quite a few ustadz who serve very enthusiastically to work at Islamic boarding schools without expecting compensation or wages. Therefore, the researcher wants to discuss the cadre formation of Islamic boarding school leaders through the Khidmah Program as a Ustadz at the Bata-Bata Panaan Palengaan Pamekasan Islamic Boarding School. The results of this research show that cadre formation in Islamic boarding school leadership is very urgent and requires special training or making it a habit of consistent and sincere activities in teaching and guiding. Khidmah as an ustadz is to train oneself as a person with moral character and to become a leader who is qualified, patient, sincere, fair and wise. The first implementation of cadre formation for Islamic boarding school leaders is recruitment, then carrying out Islamic boarding school duties according to each job that has been determined.